The Use of Oral Amino‐Bisphosphonates and Coronavirus Disease 2019 (COVID‐19) Outcomes. (22nd August 2021) - Degli Esposti, Luca; Perrone, Valentina; Sangiorgi, Diego; Andretta, Margherita; Bartolini, Fausto; Cavaliere, Arturo; Ciaccia, Andrea; Dell'orco, Stefania; Grego, Stefano; Salzano, Sara; Ubertazzo, Loredana; Vercellone, Adriano; et al.
ABSTRACT: The determinants of the susceptibility to severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2) infection and severe coronavirus disease 2019 (COVID‐19) manifestations are yet not fully understood. Amino‐bisphosphonates (N‐BPs) have anti‐inflammatory properties and have been shown to reduce the incidence of lower respiratory infections, cardiovascular events, and cancer. We conducted a population‐based retrospective observational cohort study with the primary objective of determining if oral N‐BPs treatment can play a role in the susceptibility to development of severe COVID‐19. Administrative International Classification of Diseases, Ninth Revision, Clinical ModificationI (ICD‐9‐CM) and anatomical‐therapeutic chemical (ATC) code data, representative of Italian population (9% sample of the overall population), were analyzed. Oral N‐BPs (mainly alendronate and risedronate) were included in the analysis, zoledronic acid was excluded because of the low number of patients at risk. Incidence of COVID‐19 hospitalization was 12.32 (95% confidence interval [CI], 9.61–15.04) and 11.55 (95% CI, 8.91–14.20), of intensive care unit (ICU) utilization because of COVID‐19 was 1.25 (95% CI, 0.38–2.11) and 1.42 (95% CI, 0.49–2.36), and of all‐cause death was 4.06 (95% CI, 2.50–5.61) and 3.96 (95% CI, 2.41–5.51) for oral N‐BPs users and nonusers, respectively. Sensitivity analyses that excluded patients with prevalent vertebral or hip fragility fractures and without concomitant glucocorticoid treatment yielded similar results. In conclusion, we found that the incidence of COVID‐19 hospitalization, intensive care unit (ICU) utilization, and COVID‐19 potentially related mortality were similar in N‐BPs–treated and nontreated subjects. Similar results were found in N‐BPs versus other anti‐osteoporotic drugs. We provide real‐life data on the safety of oral N‐BPs in terms of severe COVID‐19 risk on a population‐based cohort. Our results do not support the hypothesis that oral N‐BPs can prevent COVID‐19 infection and/or severe COVID‐19; however, they do not seem to increase the risk. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).